Comparative Analysis of Employees Cost of ten Nifty it Index Companies - Parulekar, Pushkar Dilip (SFIMAR Research Review, 2017)
Information Technology (IT) is an industry, based mostly on human capital as a precious resource. Most IT companies which are part of Nifty IT index are free of debt. The major component of their cost structure is employee cost. Nifty IT index consists of 10 stocks viz. HCL Technologies Limited, Infosys Limited, Justdial Limited, KPIT Technologies Limited, Mind Tree Limited, Oracle Financial Services Software Ltd., Tata Consultancy Services Limited, Tata Elxsi Limited, Tech Mahindra Limited and Wipro Limited. Employee cost as a percentage of operating income have been calculated for all these 10 companies over the period of last 10 financial years. (i.e. from year ending March 2007 to March 2016.) Single Factor ANOVA with 95 per cent confidence is used to infer the results. It is also used to study variance with respect to financial years, size of the company in terms of operating income and two combined timeframes between 2006-11 and 2011-16. Employee cost which is major cost for IT companies has increased significantly in 2011-16 as compared to 2006-11. The problem of higher employee cost is more significant in smaller companies.